Imaginário, linguagem e literatura ou conjeturas sobre um leitor insurreto (Polifonia, 2002)
ABSTRACT: In this paper, I review the treasures of a research carried out in other times with the purpose of describing the moments in which pleasure/displeasure materializies in the bodies of secondary school students during class. Here I see and hear students as they are guided to be readers of literature.